A infância: resgatando os espaços perdidos - Oliveira, Maria Aparecida Pereira (2009)
The intention of this research is to raise awareness among teachers of kindergarten and elementary grades of the important role of knowing the playgrounds as a means of guaranteeing them their rights and therefore a better life and healthier. Another proposal is to identify the role of play in developing child's psyche. For this it is necessary to know the meaning of the play, to conceptualize the key terms used to describe the act of playing, also becoming crucial to analyze the role and training of educators in the process of play. We believe that an education from the perspective of educators playful it is necessary to be thought in our institutions of higher education, with the concept of playful an educator who not only deals with curriculum issues systematized and installed in schools, but concerns to the educator who through the act of play involves students in social, political, religious, ethical and aesthetic of our society. Thus, it is expected to offer a more conscious about the importance of play in human life, especially the child's life. Closing suggest a small project which lists ideas for schools, neighborhoods and cities to promote and legitimize the participation of children and young people in building a more supportive environment for all.